Pendekatan tasawuf al-Taftazani (m. 792 H) dalam Sharh al-Arba’in al-Nawawiyyah: Analisis perbandingan dengan karya Syarah Hikam oleh Tok Pulau Manis dan Logika Agama oleh M.Quraish Shihab / Rosni Wazir - Rosni , Wazir (2018)
Al-Taftazani was a proficient scholar in Arabic and aqidah who had a tendency towards tasawuf. He had produced many works related to the Arabic language and aqidah, but there is not much information relating to his work of tasawuf. However, there is a work highlighting that aspect titled Sharh al-Taftazani ala Ahadith AlArba'in al-Nawawiyyah. This work is his description of the hadith in Al-Arba'in alNawawiyyah. This study will analyse the description of tasawuf which he did on the hadiths 1, 2, 4, 5, 11, 18, 29, 24, 27 and 31 only and the comparision with two works on tasawuf in Malay which are Syarah Hikam by Tok Pulau Manis and Logika Agama : Kedudukan Wahyu & Batas-Batas Akal dalam Islam by M.Quraish Shihab. The objective of this study is to analyse al-Arba'in al-Nawawiyyah and its position on tasawuf; to discuss al-Taftazani’s biography and his methodology of writing Sharh alTaftazani 'ala Ahadith al-Arba'in al-Nawawiyyah; to examine Syarah Hikam by Tok Pulau Manis and Logika Agama by M.Quraish Shihab; and to compare the tasawuf approach by al-Taftazani in Sharh al-Taftazani 'ala Ahadith al-Arba'in al-Nawawiyyah with Syarah Hikam by Tok Pulau Manis and Logika Agama by M.Quraish Shihab. This qualitative research will analyse data from sources obtained from books, papers, theses and dissertations, conference papers and websites. Results of the analysis shows that al-Taftazani adopted tasawuf sunni in his description, but with his own methodologies.